2003
DOI: 10.1200/jco.2003.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p53 Mutation and p53 Overexpression in Advanced Epithelial Ovarian Cancer: A Gynecologic Oncology Group Study

Abstract: Alterations in p53 are a common event in advanced epithelial ovarian cancer. A mutation in p53, but not overexpression of p53, is associated with a short-term survival benefit. Additional studies are required to define the roles that p53 plays in regulating therapeutic responsiveness and patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(126 citation statements)
references
References 43 publications
12
111
2
1
Order By: Relevance
“…Age was modeled with a restricted cubic spline (Herndon & Harrell 1995) with three knots to evaluate nonlinear effects. Also a two-level classification was used for age (O55 vs %55; Havrilesky et al 2003, Tanner et al 2006, Winter et al 2007, grading (grading 3Cundifferentiated versus grading 1C2), and histotype (serous versus non-serous). Four levels were defined for front-line therapy: no chemotherapy or other therapy; platinum; platinum/paclitaxel; platinum/paclitaxel/ topotecan.…”
Section: Prognostic Relationshipsmentioning
confidence: 99%
“…Age was modeled with a restricted cubic spline (Herndon & Harrell 1995) with three knots to evaluate nonlinear effects. Also a two-level classification was used for age (O55 vs %55; Havrilesky et al 2003, Tanner et al 2006, Winter et al 2007, grading (grading 3Cundifferentiated versus grading 1C2), and histotype (serous versus non-serous). Four levels were defined for front-line therapy: no chemotherapy or other therapy; platinum; platinum/paclitaxel; platinum/paclitaxel/ topotecan.…”
Section: Prognostic Relationshipsmentioning
confidence: 99%
“…The platinum status has also been demonstrated to influence response rates to molecularly targeted agents, such as poly(ADP-ribose) polymerase (PARP) inhibitors, where early studies of olaparib showed response rates of 69% in those with platinum-sensitive disease, compared with 45% and 23% in the platinum-resistant and refractory cohorts respectively [9]. Recent studies have investigated the role of somatic aberrations in ovarian cancer oncogenesis, with each histological subtype demonstrating distinct patterns of genomic abnormality prevalence within different pathways [10][11][12][13][14][15][16][17][18][19][20]. This molecular heterogeneity offers potential therapeutic targets for novel molecularly targeted agents in patients with advanced ovarian cancers beyond the current standard chemotherapeutic options [21].…”
Section: Introductionmentioning
confidence: 99%
“…antyonkogen, czynnik transkrypcyjny; bierze udział w regulacji mutacje obecne w ok. 40-50% nabłonkowych [24][25][26][27][28][29] transkrypcji, kontroli cyklu komórkowego; w odpowiedzi na i ok. 50-80% surowiczych raków jajnika uszkodzenie DNA prowadzi do zatrzymania cyklu komórkowego o wysokim stopniu złośliwości; w fazie G1 lub indukuje apoptozę; mutacje obecne są w ok. 50% dotychczas nie ustalono, czy jest to czynnik wszystkich nowotworów; przypuszczalnie utrata funkcji P53 prognostyczny (sprzeczne wyniki badań) może być zasadniczym krokiem w transformacji komórek z mutacją genu BRCA1 CHEK2 kinaza 2 punktu kontrolnego cyklu komórkowego; bierze udział mutacja typu missens (I157T) zwiększa ryzyko [30][31][32] w regulacji cyklu komórkowego, apoptozie, naprawie uszkodzeń zachorowania na raka jajnika o granicznej DNA indukowanych promieniowaniem jonizującym; złośliwości ok. 2,5-krotnie i ok. 2,1-krotnie w odpowiedzi na uszkodzenie fosforyluje białka P53 i Brca1, na raka jajnika o niskim stopniu złośliwości regulując funkcję supresorową tych białek histologicznej; dotychczas nie ustalono, czy jest to czynnik prognostyczny (brak wyników badań)…”
Section: Tp53unclassified